(3MhGT hJYdjbGJ Ydi TQM GdRQbGfi Ydi GdefXheI GdHjbhfjIs - (3YWjI Hf YWjI GdCLghQi GdTGaYj GdCRgQi GdHQgGfis; (3eMeO GdRQbGfjs ((3eMeO GdYhGdi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeI hjcGaF eRjOg CeG HYO ajbhd YWjI GdCLghQi gPg MhGT Ydi TQM GdQSGdI GdeSeGI HefXheI GdHjbhfi ddYGde GdQHGfi SjOi eMeO GdRQbGfi OYJ EdjgG MGLI GdWGdHjf s
(3BNQgG (B:s
(3ai TGZd Ci ai TZd TGZd HYjhH faSg Yf YjhH ZjQg hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs